Les traductions néerlandaises des romans francophones camerounais - Lievois, Katrien (Tydskrif vir Letterkunde, 2016)
In the corpus of African francophone novels that have been translated into Dutch, some 50 titles in all, the contribution of Cameroon authors is considerable. Between 1960 and 2009, nine novels by five Cameroon writers were published in Dutch. This essay to analyses these translations using the methodology of Descriptive Translation Studies (Toury) and the sociology of translation (Heilbron and Sapiro Bilan). It examines how the Cameroon novels have been integrated into the Dutch literary system, what their position is, and most of all, to what extent the paratexts of the translated novels reflect this position. The detailed analysis of the reception of the Cameroon novels within the Dutch literary system reveals that there is a marked evolution in the way in which the publications have been selected and presented to the public. First, the classics of (post)colonial literature were translated, novels dealing with the (difficult) relations between the black colonised person and the white coloniser. At a later stage, the female perspective on contemporary challenges facing Africa becomes the sole focus of the novels in the corpus. What is less straightforward to define clearly, is the place of Dutch within the larger translation trends reflecting the international visibility of the novels. All the same, it seems safe to say that English, the most dominant global language, has not played a significant role in determining the translation history of any of the novels or authors under consideration. None of the novels in the corpus was first translated into English. In fact, the languages with a central position (Heilbron and Sapiro), German and Russian before 1989, appear to have been more influential. Three of the five authors were first published in a central language: Oyono and Beyala were translated into German, whereas Beti was translated into Russian. By contrast, two authors were first translated into a (semi-)peripheral language: Werewere into Dutch and Miano into Spanish. What appears to be important for the Dutch translations is that certain agents and promotors of translation played a crucial role in this. From that perspective, Magrit de Sablonière, who translated the first two African francophone novels, certainly merits special attention, as do two book collections devoted to europhone African literature, De Derde Spreker-Serie and Afrikaanse Bibliotheek, as well as the people behind them, Sjef Theunis and Jan Kees van der Werk.